Data of biomass and content values of sandy grasslands dominated by Festuca along the Danube - Fűrész, Attila; Balogh, Dániel; Pajor, Ferenc; Péter, Norbert; Kiss, Tímea; Penksza, Károly (Animal welfare, Ethology and Housing Systems (AWETH), 2022)
Festuca taxa are important grassland species in the Pannonian vegetation and they are a dominant component of the Pannonian vegetation where conditions are too extreme. The habitats of narrow-leaved or small Festuca species are indicators of poor productivity, but they are still important from the conservation point of view. As climate change and the expansion of dry habitats increase, the importance of these grasslands is likely to rise. Our study aimed to collect cut samples of biomass from 37 areas along the Danube, beginning in the northwestern part of the Little Hungarian Plain, across the central great sandy plains of the Carpathian Basin (divided into three parts: north, middle, south) to the southernmost part of the Basin at Deliblato, Serbia. The last samples were made beyond the Carpathians on the Romanian Great Plain and Bulgaria. Weende analysis of the cut samples was carried out in the laboratory of the Department of Animal Husbandry of Szent István University. Their original dry matter and crude protein, crude fat and crude fibre content were analysed according to MSZ-6830, Harris et al. (1972) and NRC (1989), and fibre fractions (NDF, ADF, ADL) were measured. Samples were classified based on the dominant Festuca species, including separate assessments of dominant Festuca samples and separate assessments of samples with co-occurring species. Values of absolute dry matter were high in all samples of Festuca vaginata, but there was a slight increase towards the southern areas, the highest values were found in the Deliblato (DFv) sample, which were above 500 mg/kg. Crude protein values were low, in none of the samples reached the 100 mg/kg. Crude fat was the lowest, fluctuating between 18 and 25 mg/kg. Crude fibre content did not show a significant difference between the sample areas, and it was around 300 mg/kg. In contrast, there were different ratios of the fiber fraction. In general, the highest values of the fiber fraction were measured in the NDF (neutral detergent fiber) data, around 500 mg/kg. ADF (acid detergent fiber) fiber content was higher in the samples from the Danube-Tisza area (Szigetmonostror/SzFv, Sandstones TT/HFv) and decreased again towards the south. Similar ratios were observed in the amount of ADL (acid-detergent lignin). Thus, all in all, the analysed samples suggest an increasing tendency in dry matter towards the southern areas. There were also significant differences between the analysed species. Differences were detected based on the separated samples of the five Festuca species and both their component grassland samples. According to the content values these grasslands provides a suitable feed base for species of small ruminants, and within this, Festuca wagneri sample types were considered to be the most suitable.